Code-switching in university classroom interaction: A case study of the University of Dar es Salaam - Shartiely, Nikuigize Erick (Stellenbosch Papers in Linguistics Plus, 2016)
Code-switching, a common linguistic practice among multilingual speakers, occurs when a speaker alternates between two or more language varieties in a single conversation. This phenomenon manifests itself in diverse ways and to achieve different goals. It may occur within or between sentences; it may signify social aspects such as identity or solidarity among people who share values; and, as this paper demonstrates, it may serve instructional purposes. This paper examines the alternating use of English and Swahili in lectures at the University of Dar es Salaam in the context of Tanzania’s language-in-education policy, which makes English the sole language of teaching and learning in higher education. The data comprise eight recorded lectures and interviews with the lecturers teaching first-year students in the departments of Political Science and Public Administration (PSPA) and Sociology and Social Anthropology (SSA). The study was premised on the assumption that lecturers are likely to make marked language choices consciously or unconsciously with first-year students because they are new to the university’s English spoken register. The primary objective of this particular paper is to identify, describe, document and analyse the types of code-switching that lecturers used during lectures. A discourse analysis (DA) approach facilitated the identification and analysis of the lecturers’ code-switching. The findings indicate that lecturers used inter- and intra-sentential code-switching to engage with students, to translate concepts, to explain, to manage students’ behaviour, and to advise or encourage students. This paper broadens our understanding of individual and societal multilingualism and how lecturers manage it in the context of higher education in Tanzania. It highlights practical issues of English language usage in Tanzanian higher education as an instance of the use of English as an academic lingua franca in contexts where a local language dominates practically all other spheres of the speakers’ lives.